Heart Rate Variability Mainly Relates to Cognitive Executive Functions and Improves Through Exergame Training in Older Adults: A Secondary Analysis of a 6-Month Randomized Controlled Trial - Eggenberger, Patrick; Annaheim, Simon; Kündig, Kerstin A.; Rossi, René M.; Münzer, Thomas; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2020)
Heart rate variability (HRV) mirrors autonomic nervous system activities and might serve as a parameter to monitor health status in older adults. However, it is currently unknown which functional health measures, including cognitive, physical, and gait performance parameters, are most strongly related to HRV indices. This knowledge would enable implementing HRV assessments into health monitoring routines and training planning for older adults. Simultaneous cognitive–motor and exergame training may be effective to improve HRV indices, but has not been investigated yet. Eighty-nine healthy older adults (≥ 70 years of age) were randomized into three groups: 1) virtual reality video game dancing, i.e. exergaming (DANCE), 2) treadmill walking with simultaneous verbal memory training (MEMORY), or 3) treadmill walking only (PHYS). Strength and balance exercises complemented each program. Over 6 months, two weekly 1-hour training sessions were performed. HRV indices (SDNN, RMSSD, and HF power) and various measures of cognitive, physical, and gait performance were assessed at baseline, after 3 months and 6 months. Multiple linear regression analyses with planned comparisons were calculated. At baseline, 8 – 12% of HRV variance was significantly explained by cognitive executive functions and leg strength (inversely related). Verbal long-term memory, aerobic and functional fitness, and gait performance did not contribute to the model (SDNN: R2 = 0.082, p = .016; RMSSD: R2 = 0.121, p = .013; HF power: R2 = 0.119, p = .015). After 6 months, DANCE improved HRV indices, while MEMORY and PHYS did not (time×intervention interactions: first contrast DANCE/MEMORY vs. PHYS: SDNN p = .014 one-tailed, ΔR2 = 0.020 and RMSSD p = .052 one-tailed (trend), ΔR2 = 0.007; second contrast DANCE vs. MEMORY: SDNN p = .002 one-tailed, ΔR2 = 0.035, RMSSD p = .017 one-tailed, ΔR2 = 0.012, and HF power p = .011 one-tailed, ΔR2 = 0.013). We conclude that mainly cognitive executive functions are associated with HRV indices and that exergame training improves global and parasympathetic autonomic nervous system activities in older adults. Regular assessments of HRV in older citizens could be particularly beneficial to monitor cognitive health and provide indications for preventative exercise measures.